Manufacturing Organic Environmentally Friendly Electrical Circuits Using the Composites' Single‐Walled Carbon Nanotubes and PEDOT:PSS. Issue 2 (1st December 2021) - Alhashmi Alamer, Fahad; Badawi, Nujud M.
Abstract : Herein, several different methods of preparation to explore the thermal and electrical properties of cotton fabric impregnated with single‐walled carbon nanotubes (SWCNTs) and poly (3, 4 ethylenedioxy thiophene) poly(styrenesul‐fonate) (PEDOT:PSS) are used. The SWCNTs and PEDOT:PSS are delivered by the drop‐casting technique either as a mixture of these constituents or as a series of steps in which each constituent is added sequentially. The primary finding is that lower sheet resistances can be achieved by applying the constituents in sequence rather than as a mixture. For example, given fixed amounts of SWCNTs and PEDOT:PSS delivered as a mixture have sheet resistance 2.158 Ω cm −1, but when the same amounts are delivered in the order SWCNTs followed by PEDOT: PSS, the sheet resistance is reduced to 0.985 Ω cm −1, and when this order is reversed, the sheet resistance is further reduced to 0.633 Ω cm −1 . Finally, when the same total amounts of SWCNTs and PEDOT:PSS are delivered in the order SWCNTs followed by PEDOT:PSS, followed by SWCNTs, the sheet resistance is further reduced to 0.342 Ω cm −1 . Sheet resistances of the conductive cotton fabric are found to be stable over a period of 4 months at room temperature. Abstract : A novel procedure for obtaining circuit elements through the sequential addition of the constituents to achieve a cotton fabric impregnated with single‐walled carbon nanotubes and PEDOT:PSS is explained. This conductive cotton fabric has generated a sheet resistance of 0.004 Ω cm −1 at a concentration of 33.3 wt% with metallic behavior.